The influence of stress and natural fracture on a stimulated deep shale reservoir using the boundary element method - Songze Liao; Ziming Zhang; Jinghong Hu; Yuan Zhang (Natural Gas Industry B, 2025)
Hydraulic fracturing plays a critical role in enhancing shale gas production in deep shale reservoirs. Conventional hydraulic fracturing simulation methods rely on prefabricated grids, which can be hindered by the challenge of being computationally overpowered. This study proposes an efficient fracturing simulator to analyze fracture morphology during hydraulic fracturing processes in deep shale gas reservoirs. The simulator integrates the boundary element displacement discontinuity method and the finite volume method to model the fluid-solid coupling process by employing a pseudo-3D fracture model to calculate the fracture height. In particular, the Broyden iteration method was introduced to improve the computational efficiency and model robustness; it achieved a 46.6 % reduction in computation time compared to the Newton-Raphson method. The influences of horizontal stress differences, natural fracture density, and natural fracture angle on the modified zone of the reservoir were simulated, and the following results were observed. (1) High stress difference reservoirs have smaller stimulated reservoir area than low stress difference reservoirs. (2) A higher natural fracture angle resulted in larger modification zones at low stress differences, while the effect of a natural fracture angle at high stress differences was not significant. (3) High-density and long natural fracture zones played a significant role in enhancing the stimulated reservoir area. These findings are critical for comprehending the impact of geological parameters on deep shale reservoirs.